Enhancing C2 pedicle screw placement in Hangman’s fractures: a comparative study of navigation and 3D printed guidance techniques - Ruiqiang, Rao; Yi, Li; Haiyan, Xiao; Minggui, Wang; Yixiu, Liao; Song, Shang (Frontiers in Surgery, 2025)
ObjectiveThis retrospective study aimed to analyze the accuracy and safety of pedicle screw placement in upper cervical spine surgery for Hangman's fractures, particularly in cases with high-riding vertebral artery (HRVA) at C2, using navigation technology and 3D-printed patient-specific templates.MethodsWe included 33 patients with Hangman's fractures who underwent posterior cervical fixation with bone graft fusion or non-bone graft fusion surgery between January 2013 and January 2023. Patients were divided into two groups based on the intraoperative pedicle screw placement method: Group A (n = 15) utilized a navigation system, and Group B (n = 18) used a 3D printed navigation template. Clinical and radiological data were collected and compared.ResultsOne hundred and forty-four screws (66 navigated, 78 3D-printed templates) were inserted without vertebral artery, spinal cord, or nerve injury. Operative time per screw: Group A 24.0 ± 5.6 min vs. Group B 18.7 ± 4.1 min; mean difference 5.3 min (22% reduction; 95% CI −9.1 to −1.5; P = 0.018). Intra-operative blood loss:152 ± 29 ml vs. 105 ± 19 mL; mean difference 47 mL (95% CI −66 to −19; P = 0.001). Overall accuracy (Grade 0 + 1) was 98.5% (65/66) vs. 98.7% (77/78) (odds ratio 1.05; 95% CI 0.11–10.2; P = 0.97). In the Type-III fracture subgroup (8 screws per group), templates achieved 100% accuracy vs. 87.5% with navigation (P = 0.032) and lower cortical penetration (12.5% vs. 37.5%; P = 0.008). Post-operative VAS and NDI improved comparably (all inter-group P > 0.05). At 24-month follow-up, all fractures had healed; C2/3 fusion rates did not differ (facet fusion 100% vs. 100%; inter-body fusion 39% vs. 39%; P > 0.99).ConclusionThe use of 3D-printed patient-specific templates in upper cervical spine surgery for Hangman's fractures, especially in the presence of HRVA, is effective and safe. It offers comparable accuracy to navigation-assisted surgery while reducing operative time and blood loss. This approach may be particularly beneficial in minimizing the risk of vertebral artery injury and optimizing surgical outcomes. Compared to navigation technology, it can effectively improve the accuracy of screw placement in extremely unstable fractures.